2009
DOI: 10.1088/0022-3727/42/6/065102
|View full text |Cite
|
Sign up to set email alerts
|

High repetition rate femtosecond laser forming sub-10 µm diameter interconnection vias

Abstract: Laser ablative microvia formation has been widely accepted as an effective manufacturing method for interconnect via formation. Current conventional nanosecond laser microvia formation has reached its limit in terms of minimum via diameter and machining quality. Femtosecond laser has been investigated intensively for its superior machining quality and capability of producing much smaller features. However, the traditional femtosecond laser has very low power and is thus unable to meet the throughput requiremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 28 publications
3
14
0
Order By: Relevance
“…On the example of Inconel 600, it can be seen that for very short exposure times (order of seconds), the debris cohesion with the target is low. On the other hand, material ablation with longer exposure time, as a rule, resulted in a stronger debris cohesion [9]. Profilometry comparing of two targets after 7 min exposure showed that in the case of WTi, the surrounding rim equals ≈ 1.25 µm, and for Inconel 600 it was ≈ 8 µm.…”
Section: Resultsmentioning
confidence: 97%
“…On the example of Inconel 600, it can be seen that for very short exposure times (order of seconds), the debris cohesion with the target is low. On the other hand, material ablation with longer exposure time, as a rule, resulted in a stronger debris cohesion [9]. Profilometry comparing of two targets after 7 min exposure showed that in the case of WTi, the surrounding rim equals ≈ 1.25 µm, and for Inconel 600 it was ≈ 8 µm.…”
Section: Resultsmentioning
confidence: 97%
“…Morphological changes induced by femtosecond laser on WTi/Si system, show their dependence on the laser beam characteristics such as pulse duration, pulse energy, laser peak power, irradiation time (exposure)/number of accumulated pulses and laser radiation frequency (Baurle, 2011;Cheng Jian et al, 2013;Tan et al, 2009;Campbell et al, 2007). In this work, attention was focused on the influence of LRF on the morphological and compositional changes of WTi/Si system.…”
Section: Resultsmentioning
confidence: 99%
“…Initial studies in this field are focused on microvias generation, 1 microhole processing in steel and copper foils, 2 refractive index changes in transparent materials, 3 and laser ablation of microcavities. 4,5 In addition, the potential of the technology has been already demonstrated by means of specific machining examples, such as micropyramids and embossing tools.…”
Section: Introductionmentioning
confidence: 99%